Characterisation of local aluminum-alloyed contacts to silicon solar cells - Müller, Jens (2013)
Silicon solar cell, local aluminum alloying, recombination, kinetic model, laser ablation, analytic simulation. - Siliziumsolarzelle, lokale Al Legierung, Rekombination, kinetisches Modell, Laserablation, analytische Simulation
Keywords: Rekombination; Elektrischer Kontakt; Solarzelle; Silicium; Aluminiumlegierung; Hochschulschrift